1993
DOI: 10.1139/f93-254
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Lake Erie Offshore Sediments by Dreissena, and Its Ecological Implications

Abstract: Derrnott, R., and M. Munawar. 1993. Invasion of Lake Erie offshore sediments by Breissena, and its ecological implications. Can. j. Fish. Aquat. Sci. 58: 2298-2304.Large populations sf the exotic rounded (noncarinate) shelled mussel sf the genus Breissena were found to exist on soft sediments collected throughout the central and eastern basins of Lake Erie during July and August 1992. Two different phenotypes were present on fine sediments (91 50 ym) in the eastern basin. An elongated white morph was common on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(114 citation statements)
references
References 12 publications
5
107
2
Order By: Relevance
“…These relatively high impact estimates were site-specific and not likely applicable to the entire western basin. Impacts were based on a population density of about 260,000/m 2 , which is far greater than densities found in most other areas of the western basin (Dermott andMunawar 1993, Garton andHaag 1993). Reeders et al (1989) determined that Dreissena was capable of filtering the entire volume of two lakes in the Netherlands in 11 and 18 days, respectively.…”
Section: Filtration Rates Of Zebra Mussels In Saginaw Baymentioning
confidence: 93%
“…These relatively high impact estimates were site-specific and not likely applicable to the entire western basin. Impacts were based on a population density of about 260,000/m 2 , which is far greater than densities found in most other areas of the western basin (Dermott andMunawar 1993, Garton andHaag 1993). Reeders et al (1989) determined that Dreissena was capable of filtering the entire volume of two lakes in the Netherlands in 11 and 18 days, respectively.…”
Section: Filtration Rates Of Zebra Mussels In Saginaw Baymentioning
confidence: 93%
“…Mussels were cleaned of shell debris and allowed to flush sediment and gut contents overnight in aerated filtered lake water in 200 L flow-through system aquaria. Separation of mussel samples in groups of D. polymorpha and D. bugensis was performed based on the differences in ventral surface morphology, which is distinctly flattened for zebra mussels and slightly rounded for quagga mussels (Dermott and Munawar, 1993;. Except for a single harbour (H3), where the mussel population was dominated by D. polymorpha (approx.…”
Section: Dreissenid Spp Samplingmentioning
confidence: 99%
“…Although Dreissena prefer hard substrates (Mills et al 1996), it has been observed that D. bugensis can better persist in deep, offshore waters within soft substrate compared to zebra mussel (Dreissena polymorpha; Dermott and Munawar 1993). In Lake Erie, D. bugensis was abundant on sand and sandy silt at depths between 10 and 30 m, on profundal sediments beyond 40 m (Dermott and Munawar 1993) and have also been observed in Lake Ontario soft sediments down to 130 m (Mills et al 1993, Claxton andMackie 1998). In 1992, early invasion densities of D. bugensis in central Lake Erie soft sediments ranged from 0 to >10,000/m 2 with population increases in 1993 Munawar 1993, Dermott andKerec 1997).…”
Section: Quagga Mussels and Benthic Invertebrate Communitiesmentioning
confidence: 99%